Serum cholesterol concentration and coronary heart disease in population with low cholesterol concentrations. - Chen, Z (1991)
OBJECTIVE--To examine the relation between serum cholesterol concentration and mortality (from coronary heart disease and from other causes) below the range of cholesterol values generally seen in Western populations. DESIGN--Prospective observational study based on 8-13 years of follow up of subjects in a population with low cholesterol concentrations. SETTING--Urban Shanghai, China. SUBJECTS--9021 Chinese men and women aged 35-64 at baseline. MAIN OUTCOME MEASURE--Death from coronary heart disease and other causes. RESULTS--The average serum cholesterol concentration was 4.2 mmol/l at baseline examination, and only 43 (7%) of the deaths that occurred during 8-13 years of follow up were attributed to coronary heart disease. There was a strongly positive, and apparently independent, relation between serum cholesterol concentration and death from coronary heart disease (z = 3.47, p less than 0.001), and within the range of usual serum cholesterol concentration studied (3.8-4.7 mmol/l) there was no evidence of any threshold. After appropriate adjustment for the regression dilution bias, a 4 (SD 1)% difference in usual cholesterol concentration was associated with a 21 (SD 6)% (95% confidence interval 9% to 35%) difference in mortality from coronary heart disease. There was no significant relation between serum cholesterol concentration and death from stroke or all types of cancer. The 79 deaths due to liver cancer or other chronic liver disease were inversely related to cholesterol concentration at baseline. CONCLUSION--Blood cholesterol concentration was directly related to mortality from coronary heart disease even in those with what was, by Western standards, a "low" cholesterol concentration. There was no good evidence of an adverse effect of cholesterol on other causes of death.